Industry Information Diffusion and the Lead-lag Effect in Stock Returns - Hou, Kewei (Review of Financial Studies, 2007)
Journal Article Industry Information Diffusion and the Lead-lag Effect in Stock Returns Get access Kewei Hou Kewei Hou Department of Finance, Fisher College of Business, The Ohio State University Address correspondence to Kewei Hou, Department of Finance, Fisher College of Business, Ohio State University, 2100 Neil Avenue, Columbus, OH 43210, or e-mail: hou.28@osu.edu Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 20, Issue 4, July 2007, Pages 1113–1138, https://doi.org/10.1093/revfin/hhm003 Published: 22 January 2007